Microsoft Office Access 2007 : forms, reports, and queries - McFedries, Paul (Business solutions., 2007)
Offers guidelines for using Access 2007 queries, forms, and reports, utilizing a practical rather than a theoretical approach that is designed to give readers the ability to extract essential data, build efficient front-end forms for that data, and publish the results in an easy-to-read format.